Extracorporeal Membrane Oxygenation for Severe Paraquat Intoxication: A Systematic Review of Clinical Cases: A Systematic Review Study - Samsamshariat , Shiva; Ebrahimi, Faeze; Meamar, Rokhsareh; Jalali, Mohammadhadi; Eizadi-Mood, Nastaran; Massoumi, Gholamreza; Dorooshi , Gholamali; Feizi, Awat; Nouri , Rasool (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Paraquat is a widely used, inexpensive contact herbicide that can cause fulminant multi-organ failure and death after ingestion, and no specific antidote is available. Extracorporeal membrane oxygenation (ECMO) has been used sporadically as rescue therapy in patients with severe paraquat intoxication, but its impact on clinical outcomes remains uncertain. This study systematically reviews the existing evidence on ECMO use in paraquat poisoning. Methods: We searched Web of Science, PubMed, Scopus, Embase, the Cochrane Library, and Google Scholar from database inception to 1 November 2023 for human studies reporting paraquat-poisoned patients treated with ECMO. Eligible designs included case reports and case series. Two reviewers independently screened records, extracted data, and assessed methodological quality using the Joanna Briggs Institute critical appraisal tools. Quantitative synthesis was descriptive, comparing survivors and non-survivors. Results: After removal of duplicates, 21 records were screened, and 14 full-text articles were assessed for eligibility. Nine studies published between 1985 and 2023, comprising 15 ECMO-treated patients, were included. The mean age was 27.3 ± 12.4 years. Survivors started ECMO later after paraquat ingestion than non-survivors (32.6 ± 8.8 vs 7.7 ± 8.4 days, P < 0.001). Survivors also had a longer hospital stay (78.5 ± 2.1 vs 21.8 ± 33.1 days, P = 0.049). In contrast, ECMO duration, indication for ECMO, concomitant extracorporeal therapies, and ECMO configuration (veno-venous vs. veno-arterial) were not significantly associated with survival. Most survivors underwent bilateral lung transplantation during or after ECMO support. Conclusion: The limited evidence suggests that ECMO may have a role, often alongside lung transplantation, in selected patients with paraquat poisoning. Larger registries and observational studies are needed to clarify patient selection, timing, and outcomes of ECMO in this setting.